Educational Media and Technology Yearbook - Orey, Michael; Jones, Stephanie A.; Branch, Robert Maribe; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
The evolution of educational technology has seen a shift from hardware and software to tactics and techniques, as the 2010 edition of the Educational Media and Technology Yearbook makes abundantly clear. As in previous years, it offers the reader a snapshot of the moment and a look ahead to issues most likely to shape the immediate future$1 (Ban array as varied as the use of social networking sites in learning, new collaborations between media specialists and non-teaching school personnel, and the emerging discipline of Human Performance Technology. Here are ideas that are not only intellectually intriguing but also practical and practice-building, inspiring educators using computer technology to move beyond traditional teaching roles toward learning design. Included in the 2010 Yearbook: Salient issues in learning, design, and technology, such as the critical part school leadership plays in instructors$1 (Bacceptance or rejection of technology New trends in library and information science, including the role of school library media centers in preventing cyberbullying This year$1 (Bs leadership profiles: Jerrold Kemp, author of Designing Effective Instruction; W. Michael Reed, accomplished, dedicated, and recognized educator in instructional technology A worldwide directory of current professional associations and organizations in learning design, technology, information, and library science Up-to-date listings of graduate program in these fields, rated using a variety of criteria Special mediagraphy section featuring journals, ERIC documents, and media-related publications in specialized areas, including distance education, simulation/virtual reality, artificial intelligence, special education, and professional development Academics in learning design and technology, and information and library science will welcome the latest edition of the Educational Media and Technology Yearbook as a reference, idea book, and a panoramic study of where we are now.s
Trends and Issues in Learning, Design, and Technology -- Understanding School Leaders$1 (BRole in Teachers$1 (BAdoption of Technology Integration Classroom Practices -- Issues and Trends in Instructional Technology: Growth and Maturation of Web-Based Tools in a Challenging Climate; Social Networks Gain Educators$1 (BAttention -- Rapid Prototyping for Designing and Delivering Technology-Based Lessons -- Theory-Based Evaluation of Instruction: Implications for Improving Student Learning Achievement in Postsecondary Education -- Developing Technology Fluency in Community Practice: Exploration of the (3z(BPaintbrush(3y (BMetaphor -- The Instructional and Learning Technologies Department (ILT) in the College of Education, Sultan Qaboos University -- Learning with Technology: Learner Voice and Agency -- Trends in Performance Improvement: Expanding the Reach of Instructional Design and Technology -- Trends and Issues in Library and Information Science -- School Library Media Specialists and School Counselors: Collaborative Partners to Expand Distance Education Opportunities for High School Students -- The Role of the School Library Media Center Program in the Education and Prevention of Cyberbullying -- E-Government, Government Documents, and School Libraries -- Leadership Profiles -- Jerrold Kemp: Designing Effective Instruction -- W. Michael Reed: At the Beginnings Using Computers in Education for Higher-Order Learning -- Organizations and Associations -- Worldwide List of Organizations in Learning, Design, Technology, Information, or Libraries -- Graduate Programs -- Worldwide List of Graduate Programs in Learning, Design, Technology, Information, or Libraries -- Mediagraphy: Print and Nonprint Resources -- Mediagraphy.s
Keywords: Education; Education; Educational Technology; Learning & Instruction